Synthesis Of A Schiff Base Derivade From Dopamine And Cinamaldehyde - Tulcán Mejía, Eliana Maritza; Galindo Cruz, Johan Fabian; Perez Figueredo, Carmen Rosa (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In this research paper, evidences of the synthesis of a Schiff's base from dopamine and cinnamaldehyde, synthesized via wet condensation are reported. This compound was analyzed by infrared and visible ultraviolet spectroscopy; the experimental results were compared with those obtained by the Density Functional Theory (DFT) method. The analyzes allowed the research to confirm the obtained specie: 4-(2-{[(1E,2E)-3-phenylprop-2-en-1-ylidene]amino}ethyl)benzene-1,2-diol.